Low risk of the TMPRSS2 inhibitor camostat mesylate and its metabolite GBPA to act as perpetrators of drug-drug interactions - Weiß, Johanna; Bajraktari-Sylejmani, Gzona; Haefeli, Walter E. (Chemico-biological interactions, 2021)
Camostat mesylate, a potent inhibitor of the human transmembrane protease, serine 2 (TMPRSS2), is currently under investigation for its effectiveness in COVID-19 patients. For its safe application, the risks of camostat mesylate to induce pharmacokinetic drug-drug interactions with co-administered drugs should be known. We therefore tested in vitro the potential inhibition of important efflux (P-glycoprotein (P-gp, ABCB1), breast cancer resistance protein (BCRP, ABCG2)), and uptake transporters (organic anion transporting polypeptides OATP1B1, OATP1B3, OATP2B1) by camostat mesylate and its active metabolite 4-(4-guanidinobenzoyloxy)phenylacetic acid (GBPA). Transporter inhibition was evaluated using fluorescent probe substrates in transporter over-expressing cell lines and compared to the respective parental cell lines. Moreover, possible mRNA induction of pharmacokinetically relevant genes regulated by the nuclear pregnane X receptor (PXR) and aryl hydrocarbon receptor (AhR) was analysed in LS180 cells by quantitative real-time PCR. The results of our study for the first time demonstrated that camostat mesylate and GBPA do not relevantly inhibit P-gp, BCRP, OATP1B1 or OATP1B3. Only OATP2B1 was profoundly inhibited by GBPA with an IC50 of 11 μM. Induction experiments in LS180 cells excluded induction of PXR-regulated genes such as cytochrome P450 3A4 (CYP3A4) and ABCB1 and AhR-regulated genes such as CYP1A1 and CYP1A2 by camostat mesylate and GBPA. Together with the summary of product characteristics of camostat mesylate indicating no inhibition of CYP1A2, 2C9, 2C19, 2D6, and 3A4 in vitro, our data suggest a low potential of camostat mesylate to act as a perpetrator in pharmacokinetic drug-drug interactions. Only inhibition of OATP2B1 by GBPA warrants further investigation.